Предмет: Алгебра, автор: djenirollol

СРОЧНО ПОЖАЛУЙСТА!!!!!!!!!!!

Приложения:

Ответы

Автор ответа: evgenrubalko11
0

19ab(20 {a}^{2}  -  {b}^{2} ) + 20ab( {b}^{2}  - 19 {a}^{2} ) = 380 {a}^{3}b - 19a {b}^{3}  + 20a {b}^{3}  - 380 {a}^{3} b = a {b}^{3}  = 10 \times ( { - 5)}^{3}  =  - 1250

Автор ответа: krampus777
0

Ответ:

-1250

Объяснение:

19ab(20 {a}^{2}  -  {b}^{2} ) + 20ab( {b}^{2}  - 19 {a}^{2} ) \\ 380 {a}^{3} b - 19a {b}^{3}  + 20a {b}^{3}  - 380 {a}^{3} b \\ a {b}^{3}  \\ 10 \times ( - 5 {)}^{3}  =  - 10 \times 125 =  - 1250

Похожие вопросы
Предмет: Геометрия, автор: 1999kuziko1999
Предмет: Математика, автор: Milka36453